Predominant palmoplantar lichen planus: A diagnostic challenge - Rameshwar Gutte; Uday Khopkar (Wolters Kluwer Medknow Publications, 2014)
Background: Palmoplantar lesions in lichen planus (LP) are uncommon. In such cases, diagnosis is usually missed. This study was conducted to document various clinical and histopathological features of palmoplantar LP. Materials And Methods: A total of 18 patients from our outpatient department with lesions of LP, either predominantly or exclusively on palms and/or soles were studied. Patients with history of drug intake in recent past and patients with classical acute widespread LP with a few lesions on palms or soles were excluded. In each patient, diagnosis was made on clinicopathological correlation. Various clinical and histopathological features were analyzed. Results: Average age of onset was 38 years. Male: female ratio was 1:0.6 and average disease duration was 11 months. Exclusive palm or sole involvement was seen in 4/18 patients. Itching was the most common symptom. Clinically the most common variant was hypertrophic. Histologically presence of parakeratosis, spongiosis, lack of melanophages, and lack of hypergranulosis in some cases was seen in addition to classical features of LP. In 3 out of 4 patients with exclusive palmoplantar involvement diagnosis of LP was missed clinically. Conclusion: Involvement of palms and soles in LP poses a diagnostic challenge due to variable presentations. Histopathology is of vital importance for correct diagnosis and treatment.